The Influence of E-Marketing and Competitive Environment on Marketing Performance of MSME Products (Case Study of Product of Cireng as MSMEs in Jakarta) - Meitolo Hulu; Axel Yunior San; Michelle (Politeknik Pariwisata Palembang, 2024)
This study aims to analyze the effect of e-marketing and competitive environment on marketing performance. In this study using a quantitative approach with purposive sampling technique. The number of samples selected was based on the capacity as a Cireng product business actor who experienced the sales process directly, and competition in marketing Cireng. The number of samples selected is thirty people who are Cireng business actors in Jakarta. The results show that e-marketing has a positive and significant effect of 21,3 % on marketing performance. Likewise, the competitive environment variable which has a positive and significant effect of 61,9 on marketing performance. Cireng business actors as a product of MSMEs need to pay attention to the competition that occurs around their business, in addition to increasing marketing on social media so that consumers can know and have more confidence in quality Cireng products.